2011
DOI: 10.1016/j.bbamcr.2011.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Functional modulation of AMP-activated protein kinase by cereblon

Abstract: Mutations in cereblon (CRBN), a substrate binding component of the E3 ubiquitin ligase complex, cause a form of mental retardation in humans. However, the cellular proteins that interact with CRBN remain largely unknown. Here, we report that CRBN directly interacts with the α1 subunit of AMP-activated protein kinase (AMPK α1) and inhibits the activation of AMPK activation. The ectopic expression of CRBN reduces phosphorylation of AMPK α1 and, thus, inhibits the enzyme in a nutrient-independent manner. Moreover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
90
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(101 citation statements)
references
References 44 publications
8
90
2
1
Order By: Relevance
“…8). These findings not only strengthen the idea that CRBN is an endogenous negative regulator of AMPK (4,5), but also provide a testable hypothesis regarding the mechanism by which the nonsense mutation in CRBN causes mental deficit in humans (Fig. 9).…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…8). These findings not only strengthen the idea that CRBN is an endogenous negative regulator of AMPK (4,5), but also provide a testable hypothesis regarding the mechanism by which the nonsense mutation in CRBN causes mental deficit in humans (Fig. 9).…”
Section: Discussionsupporting
confidence: 59%
“…Furthermore, in whole-body Crbn-deficient mice, we also observed severe deficits in behaviors involving hippocampal function, but no noticeable abnormalities in motor function. 4 Despite its potential involvement in higher brain function, however, the cellular roles of CRBN in the central nervous system are still controversial, and the functional consequences of the C-terminal deletion found in mutant CRBN have never been characterized.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PEXs are associated with energy metabolism. Interestingly, CRBN has been reported to associate with and negatively regulate AMP-activated protein kinase, 29 which play a role in cellular energy homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that CRBN can directly interact with several proteins, such as AMP-activated protein kinase (10), the large conductance calcium-activated potassium channel (11), voltage-gated chloride channels (12), and the 20 S core proteasome subunit ␤ type 4 (13). None of these proteins has yet been shown to be targeted by CRL4 as a result of their binding to CRBN.…”
mentioning
confidence: 99%